2022
DOI: 10.1021/acsanm.2c02763
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Induced Silver Deposition on Gold Nanorods for Naked-Eye and Smartphone Detection of Acrylamide in Food

Abstract: Acrylamide is a probable human carcinogen with a wide occurrence in commonly consumed food. Because of the lack of specific antibodies against acrylamide, immunoassays usually measure acrylamide derivates, which require long derivatization times at elevated temperatures. One exception is xanthylacrylamide (XAA), which can be derived from acrylamide at room temperature within 30 min. Here, we present the development of a monoclonal antibody against XAA and a competitive enzyme-linked immunosorbent assay (ELISA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Yang et al developed a colorimetric immunosensor for PSA detection based on the ALP-mediated reduction of Ag + ions and deposition of ultrathin Ag shells on AuNRs [ 158 ]. Fu et al reported a competitive colorimetric immunoassay for the detection of xanthylacrylamide (XAA) based on the monoclonal antibody (mAb) against XAA and the multicolor change of AuNRs [ 152 ]. As shown in Figure 20 B, the mAb against XAA was labeled with ALP and used in the competitive immunoassay.…”
Section: Colorimetric Immunoassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al developed a colorimetric immunosensor for PSA detection based on the ALP-mediated reduction of Ag + ions and deposition of ultrathin Ag shells on AuNRs [ 158 ]. Fu et al reported a competitive colorimetric immunoassay for the detection of xanthylacrylamide (XAA) based on the monoclonal antibody (mAb) against XAA and the multicolor change of AuNRs [ 152 ]. As shown in Figure 20 B, the mAb against XAA was labeled with ALP and used in the competitive immunoassay.…”
Section: Colorimetric Immunoassaysmentioning
confidence: 99%
“…Copyright 2019 American Chemical Society. ( B ) Schematic illustration of the competitive colorimetric ELISA for detection of XAA based on the multicolor change of AuNRs [ 152 ]. Copyright 2022 American Chemical Society.…”
Section: Figures Schemes and Tablesmentioning
confidence: 99%